Triple Helix Collaboration in the Creation and Development of Regional Excellent Products by the Hand-Painted Batik Craftsmen Group - Pryo Handoko; Nina Kurnia; Reni Tania; Rizal Bahtiar; Topik Hidayat (Publik : (Jurnal Ilmu Administrasi), 2025)
Banten Province ranks 7th out of 10 provinces with the most batik industries in Indonesia. This position indicates that Banten batik has significant economic and cultural potential. However, the development of hand-drawn batik still faces various obstacles, including fluctuations in raw materials, limited marketing, a decline in the number of artisans, low skills in motif and dye development, and limited capital. However, Banten batik has historical uniqueness because its motifs are inspired by cultural artifacts and the history of the Banten Sultanate. The complexity of these issues and potentials demands the involvement of various actors and sectors. This research aims to identify triple-helix collaboration patterns among government, academic, and business actors in the creation and development of regional batik flagship products. The method used is a qualitative approach with descriptive analysis. The research results show that inter-sectoral synergy plays an important role in enhancing production capacity, design innovation, access to capital, and market expansion, thereby strengthening the competitiveness of Banten batik as a regional flagship product.